Th17/Treg imbalance in inflammatory bowel disease: immunological mechanisms and microbiota-driven regulation - Hu, Yuyuan; Yang, Yuhang; Li, Yan; Zhang, Qiang; Zhang, Wei; Jia, Jinghan; Han, Zhuoyi; Wang, Jinxi (Frontiers in Immunology, 2025)
Inflammatory bowel disease (IBD) is a group of conditions characterized by chronic and recurrent intestinal inflammation, primarily including Crohn’s disease (CD) and ulcerative colitis (UC). The pathogenesis of IBD is closely linked to abnormal immune responses, particularly T-cell mediated immune reactions. Th17 cells promote persistent intestinal inflammation by secreting pro-inflammatory cytokines such as IL-17, while regulatory T (Treg) cells help maintain immune homeostasis by secreting anti-inflammatory cytokines like IL-10 and TGF-β. In patients with IBD, Th17 cell function is enhanced, whereas Treg cell function is impaired or their numbers are reduced, leading to an imbalance in the immune system and exacerbating intestinal inflammation. The gut microbiota plays a crucial role in the immune regulation of IBD. Dysbiosis can lead to excessive activation of Th17 cells and suppression of Treg cell function, further aggravating clinical symptoms. Studies have shown that restoring gut microbiota balance through probiotics, antibiotics, dietary interventions, or fecal microbiota transplantation can not only improve immune responses but also restore the balance between Th17 and Treg cells, which has a positive impact on IBD treatment. This review summarizes how gut microbiota modulates the Th17/Treg cell balance to influence IBD immune responses and explores therapeutic strategies targeting Th17/Treg balance, including cytokine antagonists and immunosuppressive agents, which provide new directions and approaches for clinical IBD treatment.